Prevalence and pattern of cardiovascular risk factors in a population in India. Issue 2 (14th September 2017) - Khetan, Aditya; Zullo, Melissa; Hejjaji, Vittal; Barbhaya, Dweep; Agarwal, Sushil; Gupta, Rishab; Madan Mohan, Sri Krishna; Josephson, Richard
Abstract : Background: Cardiovascular disease is the leading cause of mortality in India. Since it is largely driven by risk factors such as hypertension, diabetes and smoking, it is important to study the treatment cascade for these conditions and identify areas for improvement. Methods: This is a cross-sectional study from Project SEHAT (Study to Enhance Heart Associated Treatments), an ongoing cluster randomised controlled trial testing the hypothesis that a community health worker-led intervention can improve the control of cardiovascular risk factors in a community in West Bengal, India. For the baseline data, 3556 adults, between the ages of 35 and 70, were screened for hypertension, diabetes and smoking. For hypertension and diabetes, an elevated reading was confirmed on a repeat visit. Results: 18.3% (n=650), 9.0% (n=317) and 14.1% (n=500) of adults were diagnosed with hypertension, diabetes and smoking, respectively. Overall, 35.0% (n=1242) adults had at least one of the three risk factors. 55.1% (n=358) of participants with hypertension and 40.4% (n=128) of participants with diabetes were unaware of their respective condition. 36.6% (n=238) of those with hypertension and 58.0% (n=184) of diabetics were on treatment. 8.2% (n=53) hypertensives were controlled (blood pressure <140/90 mm Hg) while 13.6% (n=43) diabetics were controlled (defined as fasting blood sugar <126 mg/dL). Less than 1% diabetics were on insulin, and average number of medications for a patient with hypertension was 1.2. Conclusions: In our population in semiurban India, one in three adults have a major cardiovascular risk factor, with low control rates. There is a large burden of undiagnosed cardiovascular risk factors and a large gap between treatment and control, which may be explained by lack of treatment intensification.